Political Consequences of Survival Strategies among the Urban Poor. Issue 5 (October 2018) - Desmond, Matthew; Travis, Adam
Combining ethnographic and statistical methods, this study identifies interlocking mechanisms that help explain how disadvantaged neighborhoods influence their residents' political capacity. Support systems that arise in low-income neighborhoods promote social interaction that helps people make ends meet, but these systems also expose residents to heavy doses of adversity, which dampens perceptions of collective political capacity. For the poorest residents of these neighborhoods in particular, the expected positive effect of informal social support is suppressed by the negative effect of perceived trauma. These findings present a micro-level account of poverty, social interaction, and political capacity, one that holds implications for scholarship and public policy on participatory inequality.